Accessibility: Students with Disabilities in Universities in Canada - Hill, Jennifer Leigh (Canadian Journal of Higher Education, 1992)
Data indicate that the number of students with disabling conditions in postsecondary institutions is increasing. The efforts made by universities across Canada were examined to ensure that special needs students are able to access higher education programs. Services offered by the Office for Students with Disabilities at 27 Canadian universities were investigated. Physical accessibility for students with a wide range of handicapping conditions also was explored.